Enteric neuroplasticity in seawater‐adapted European eel (Anguilla anguilla). Issue 2 (23rd October 2013) - Sorteni, C.; Clavenzani, P.; De, R.; Portnoy, O.; Sirri, R.; Mordenti, O.; Di, A.; Parmeggiani, A.; Menconi, V.; Chiocchetti, R.
Abstract European eels live most of their lives in freshwater until spawning migration to the Sargasso Sea. During seawater adaptation, eels modify their physiology, and their digestive system adapts to the new environment, drinking salt water to compensate for the continuous water loss. In that period, eels stop feeding until spawning. Thus, the eel represents a unique model to understand the adaptive changes of the enteric nervous system (ENS) to modified salinity and starvation. To this purpose, we assessed and compared the enteric neuronal density in the cranial portion of the intestine of freshwater eels (control), lagoon eels captured in brackish water before their migration to the Sargasso Sea (T0), and starved seawater eels hormonally induced to sexual maturity (T18; 18 weeks of starvation and treatment with standardized carp pituitary extract). Furthermore, we analyzed the modification of intestinal neuronal density of hormonally untreated eels during prolonged starvation (10 weeks) in seawater and freshwater. The density of myenteric (MP) and submucosal plexus (SMP) HuC/D‐immunoreactive (Hu‐IR) neurons was assessed in wholemount preparations and cryosections. The number of MP and SMP HuC/D‐IR neurons progressively increased from the freshwater to the salty water habitat (control > T0 > T18; P < 0.05). Compared with freshwater eels, the number of MP and SMP HuC/D‐IR neurons significantly increased (P < 0.05) in the intestine of starved untreated salt water eels. In conclusion, high salinity evokes enteric neuroplasticity as indicated by the increasing number of HuC/D‐IR MP and SMP neurons, a mechanism likely contributing to maintaining the body homeostasis of this fish in extreme conditions.